Đặt \(x\left(x^2+1\right)-3\left(x^2+1\right)=0\)
Ta có: \(x\left(x^2+1\right)-3\left(x^2+1\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(x^2+1\right)=0\)
Vì \(x^2\ge0\forall x\)\(\Rightarrow x^2+1\ge1\forall x\)
\(\Rightarrow\)Để \(\left(x-3\right)\left(x^2+1\right)=0\)thì \(x-3=0\)\(\Leftrightarrow x=3\)
Vậy nghiệm của đa thức đã cho là \(x=3\)
Con chỉ biết giải thế này thôi.
\(x\left(x^2+1\right)-3\left(x^2+1\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(x^2+1\right)=0\)
TH1 : \(x-3=0\Leftrightarrow x=3\)
TH2 : \(x^2+1=0\Leftrightarrow x^2=-1\left(voli\right)\)
Vậy nghiệm của đa thức là 3